Hello there! Given the expression, we can solve through a series of steps:
1. Simplify
-5 + 7 • 1
2. Multiply (according to order of operations)
7 • 1 = 7
3. Add
-5 + 7 = 2
Your final answer is 2. Hope this helps!
The answer to the question is 20.55
You didn't give any choices, but the equation looks like this: 17 = 2x + 5. Solving that for x tells you that he went on a big water slide 6 times. 2 times 6 plus 5 is the $17 he spent at the park. See how well that works out?
Answer: ![{\boxed{h(x+4)=\frac{9+3x}{8+x}}}](https://tex.z-dn.net/?f=%7B%5Cboxed%7Bh%28x%2B4%29%3D%5Cfrac%7B9%2B3x%7D%7B8%2Bx%7D%7D%7D)
Concept:
In a function f(x), it represents a function in terms of x or for x. Therefore, to find the values in the function, substitute values within the parenthesis to solve.
Solve:
<u>Given information</u>
![h(x)=\frac{-3+3x}{4+x}](https://tex.z-dn.net/?f=h%28x%29%3D%5Cfrac%7B-3%2B3x%7D%7B4%2Bx%7D)
<u>Need to find</u>
![h(x+4)](https://tex.z-dn.net/?f=h%28x%2B4%29)
<u>Substitute (x + 4) to the position of x</u>
![h(x+4)=\frac{-3+3(x+4)}{4+(x+4)}](https://tex.z-dn.net/?f=h%28x%2B4%29%3D%5Cfrac%7B-3%2B3%28x%2B4%29%7D%7B4%2B%28x%2B4%29%7D)
<u>Distributive property on the numerator</u>
![h(x+4)=\frac{-3+3x+12}{4+(x+4)}](https://tex.z-dn.net/?f=h%28x%2B4%29%3D%5Cfrac%7B-3%2B3x%2B12%7D%7B4%2B%28x%2B4%29%7D)
<u>Combine like terms</u>
![h(x+4)=\frac{-3+12+3x}{4+4+x}](https://tex.z-dn.net/?f=h%28x%2B4%29%3D%5Cfrac%7B-3%2B12%2B3x%7D%7B4%2B4%2Bx%7D)
![\boxed{h(x+4)=\frac{9+3x}{8+x}}](https://tex.z-dn.net/?f=%5Cboxed%7Bh%28x%2B4%29%3D%5Cfrac%7B9%2B3x%7D%7B8%2Bx%7D%7D)
Hope this helps!! :)
Please let me know if you have any questions